Protruding ball-mounting wafer thinning adhesive tape, preparation method thereof and wafer thinning machine
By constructing a heat/light-cured interpenetrating polymer network for the raised ball wafer thinning tape, the problems of microcracks and warping during the thinning process of raised ball wafers are solved, achieving higher processing stability and yield.
Patent Information
- Application Number
- CN202511718116.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-21
- Publication Date
- 2025-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the wafer thinning process with raised ball bearings, existing thinning tapes cause microcracks or warping to occur in specific areas of the wafer, affecting yield and processing stability.
A raised ball-planted wafer thinning tape is used, comprising a substrate film, a non-adhesive layer and a release film. The non-adhesive layer is composed of first and second polymer networks, a thermosetting agent and a photoinitiator. By constructing a thermo/photocurable interpenetrating polymer network, the cohesive strength and interfacial bonding of the adhesive layer are enhanced, and stress concentration is reduced.
It significantly reduces the probability of microcracks and warping in raised ball wafers during the thinning process, improves the mechanical integrity and processing stability of the wafer, simplifies the process flow, and increases production efficiency.
Smart Images

Figure CN121160243A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of adhesive tape, in particular to a bump ball wafer thinning adhesive tape, a preparation method thereof and a wafer thinning machine. BACKGROUND
[0002] With the rapid development of semiconductor technology, chips are evolving towards three-dimensional integration and high-density packaging. In this process, the ultra-thinning of wafers carrying active circuits is a key process for realizing multi-layer chip stacking.
[0003] In the prior art, the front surface of some wafers has been prepared with bumps or solder balls (precise micron-level three-dimensional structures, i.e., bump ball wafers, for signal interconnection before back surface thinning.
[0004] In order to protect these fragile front surface structures during back surface grinding and effectively fix the wafer, a pre-prepared thinning adhesive tape is usually used. The standard process flow is as follows: before thinning, the protective adhesive tape is first attached to the front surface of the wafer by a film attachment device, and then the wafer with the adhesive tape is sent to the wafer thinning machine for back surface grinding. The adhesive tape needs to provide stable and reliable adhesion and support during grinding.
[0005] However, when the conventional pre-prepared thinning adhesive tape is applied to wafers with micron-level bump arrays, the following problems exist: during subsequent ultra-thinning grinding, the wafer, especially large-size, thin wafers, are prone to develop micro-cracks or produce unpredictable warping in certain areas, resulting in yield reduction or even wafer breakage. The occurrence of such defects has a certain randomness, which seriously restricts the limit of wafer thinning thickness and the stability and repeatability of the processing process. SUMMARY
[0006] The main purpose of the present application is to provide a bump ball wafer thinning adhesive tape, which aims to reduce the probability of developing micro-cracks or warping in certain areas when the bump ball wafer is thinned using this adhesive tape.
[0007] To achieve the above-mentioned purpose, the present application provides a bump ball wafer thinning adhesive tape, which comprises a base film, a tack-reducing adhesive layer and a release film. The thinning adhesive tape comprises a base film, a tack-reducing adhesive layer and a release film. The tack-reducing adhesive layer comprises, by weight fraction: 60-80 parts of a first polymer network, 15-35 parts of a second polymer network, 0.5-1.5 parts of a thermal curing agent and 3-5 parts of a photoinitiator. The first polymer network comprises, by weight fraction: 70-85 parts of a soft monomer, 5-15 parts of a hard monomer, 5-15 parts of a functional monomer and a grafting monomer. The second polymer network comprises 1,5-pentanediol and fumaryl chloride.
[0008] Optionally, the adhesive layer further comprises 1-5 parts by weight of a polar monomer, the polar monomer comprising acrylic acid.
[0009] Optionally, the substrate film is a polyolefin film or a polyethylene terephthalate film, the substrate film having a thickness of 50 µm to 150 µm.
[0010] Optionally, the release film comprises a polyethylene terephthalate film or a polypropylene film, the release film having a thickness of 15 µm to 50 µm.
[0011] Optionally, the thermal curing agent comprises a trimeric isocyanate, and the photoinitiator is 1-hydroxycyclohexyl phenyl ketone.
[0012] Optionally, the soft monomer comprises isooctyl acrylate and n-butyl acrylate, the hard monomer is methyl methacrylate, and the functional monomer comprises hydroxyethyl acrylate.
[0013] Optionally, the grafting monomer comprises isocyanatoethyl methacrylate, and the grafting monomer is added in an amount of 40-80 mol% of the molar amount of the functional monomer.
[0014] To achieve the above object, the application further provides a preparation method, comprising the following steps: preparing a first polymer network; preparing a second polymer network; mixing the first polymer network, the second polymer network, a thermal curing agent, and a photoinitiator to obtain an adhesive composition; coating the adhesive composition on a convex ball mounting surface of a wafer in a wafer thinning machine to form a liquid film; laminating the substrate film on the liquid film; laminating a release film on an upper surface of a fixing module in the wafer thinning machine; mounting the wafer with the substrate film on the release film in the wafer thinning machine, and performing a heating treatment on the laminated wafer to directly form a cured adhesive tape on the wafer.
[0015] Optionally, the preparation of the second polymer network comprises the following steps: dissolving 1,5-pentanediol and triethylamine in anhydrous tetrahydrofuran under nitrogen protection at 0-5°C; adding dropwise a fumaryl chloride solution dissolved in tetrahydrofuran; continuing the reaction at 30°C for 2.5 hours; After the reaction is completed, the triethylamine hydrochloride is removed by filtration, and the tetrahydrofuran is removed by distillation under reduced pressure to obtain a second polymer network.
[0016] To achieve the above object, the application further provides a wafer thinning machine, which comprises: A fixing module for fixing and supporting; A coating module for coating an adhesive composition on the convex ball mounting surface of the wafer to form a liquid film; A laminating module for laminating the base film on the liquid film, and laminating a release film on the upper surface of the fixing module in the wafer thinning machine; A positioning module for mounting the wafer with the base film on the release film; The fixing module is further used for heating the laminated wafer to directly form a cured thinning adhesive tape on the wafer.
[0017] The carboxylic acid group forms a hydrogen bond with the hydroxyl group in the first polymer network, thereby enhancing the crosslinking density inside the adhesive layer, improving the overall cohesive strength of the adhesive layer, and strengthening the interface combination of the first polymer network and the second polymer network through the reaction of the carboxylic acid group and the isocyanate group of the grafting monomer to generate a urethane structure. The application further provides a wafer thinning method, which comprises the following steps: BRIEF DESCRIPTION OF DRAWINGS
[0018] Figure 1 The flowchart of the preparation method in Example 1 of the application is shown in the figure. Figure 2 The structural diagram of the wafer thinning machine in Example 4 of the application is shown in the figure.
[0019] Reference signs: 1, fixing module; 2, coating module; 3, laminating module; and 4, positioning module.
[0020] The implementation, functional features and advantages of the application will be further described with reference to the embodiments and the accompanying drawings. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by a person of ordinary skill in the art without creative work fall within the protection scope of the present application.
[0022] Unless otherwise specified, the "parts" in the embodiments of the present application are all weight parts. The reagents used are commercially available reagents in the art.
[0023] In addition, if the present application has a description of "first", "second" and the like in the embodiments, the description of "first", "second" and the like is only for the purpose of description, and cannot be understood as indicating or implying the relative importance of the indicated technical features or implicitly indicating the number of the indicated technical features. Therefore, the features limited by "first", "second" can explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing throughout the text includes three parallel schemes. For example, "A and / or B" includes A scheme, or B scheme, or A and B simultaneously meet the scheme. In addition, the technical solutions of each embodiment can be combined with each other, but it must be based on the realization of a person of ordinary skill in the art. When the combination of technical solutions appears contradictory or unachievable, it should be considered that the combination of technical solutions does not exist, and is not within the protection scope required by the present application.
[0024] The present application provides a convex ball-plant wafer thinning adhesive tape, the thinning adhesive tape comprising a substrate film, an adhesion-reducing glue layer and a release film; The adhesion-reducing glue layer comprises, by weight parts: 60-80 parts of a first polymer network, 15-35 parts of a second polymer network, 0.5-1.5 parts of a thermal curing agent and 3-5 parts of a photoinitiator; The first polymer network comprises, by weight parts: 70-85 parts of a soft monomer, 5-15 parts of a hard monomer, 5-15 parts of a functional monomer and a grafting monomer. The second polymer network comprises 1,5-pentanediol and fumaric chloride.
[0025] Preferably, the adhesion-reducing glue layer further comprises 1-5 parts by weight of a polar monomer, the polar monomer comprising acrylic acid.
[0026] Preferably, the substrate film is a polyolefin film or a polyethylene terephthalate film, and the thickness of the substrate film is 50 µm to 150 µm.
[0027] Preferably, the release film comprises a polyethylene terephthalate film or a polypropylene film, and the thickness of the release film is 15 µm to 50 µm.
[0028] Preferably, the thermal curing agent comprises a trimeric isocyanate, and the photoinitiator is 1-hydroxycyclohexyl phenyl ketone.
[0029] Preferably, the soft monomer comprises isooctyl acrylate and n-butyl acrylate, the hard monomer is methyl methacrylate, and the functional monomer comprises hydroxyethyl acrylate.
[0030] Preferably, the grafting monomer comprises isocyanatoethyl methacrylate, and the grafting monomer is added in an amount of 40-80 mol% of the molar amount of the functional monomer.
[0031] In the present application, the content of the polar monomer can be any value between 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, and 5 parts by weight.
[0032] The content of the first polymer network in the tack-reducing adhesive layer of the present application can be any value between 60 parts by weight, 70 parts by weight, and 80 parts by weight.
[0033] The content of the second polymer network in the tack-reducing adhesive layer of the present application can be any value between 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, and 35 parts by weight.
[0034] The content of the thermal curing agent in the tack-reducing adhesive layer of the present application can be any value between 0.5 parts by weight, 1 part by weight, and 1.5 parts by weight.
[0035] The content of the photoinitiator in the tack-reducing adhesive layer of the present application can be any value between 3 parts by weight, 4 parts by weight, and 5 parts by weight.
[0036] The content of the soft monomer in the first polymer network of the present application can be any value between 70 parts by weight, 75 parts by weight, 80 parts by weight, and 85 parts by weight.
[0037] The content of the hard monomer in the first polymer network of the present application can be any value between 5 parts by weight, 10 parts by weight, and 15 parts by weight.
[0038] The content of the functional monomer in the first polymer network of the present application can be any value between 5 parts by weight, 10 parts by weight, and 15 parts by weight.
[0039] The content of the polar monomer in the first polymer network of the present application can be any value between 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, and 5 parts by weight.
[0040] The thickness of the substrate film of the present application can be any value between 50 µm, 60 µm, 70 µm, 80 µm, 90 µm, 100 µm, 110 µm, 120 µm, 130 µm, 140 µm, and 150 µm.
[0041] The thickness of the release film can be any value between 15 µm, 20 µm, 25 µm, 30 µm, 35 µm, 40 µm, 45 µm and 50 µm.
[0042] The amount of the grafting monomer added can be any value between 40 mol%, 50 mol%, 60 mol%, 70 mol% and 80 mol% of the molar amount of the functional monomer.
[0043] It should be noted that in the conventional existing wafer thinning process, the wafer with micron-level bump array is prone to local stress concentration in the backside grinding stage due to the mismatch between the viscoelasticity of the adhesive layer and the three-dimensional structure of the surface. The adhesive layer cannot effectively disperse shear force and normal stress under dynamic mechanical load, resulting in non-uniform deformation field in the edge and bump array area of the wafer, and causing interface delamination and plastic deformation of the substrate material. The above phenomenon directly leads to a sharp decrease in structural stiffness when the wafer is thinned to a critical thickness, and the vibration energy accumulates in the lattice defects during the grinding process to form a micro-crack propagation path.
[0044] Specifically, when a pre-made thinning adhesive tape is used to process a 12-inch wafer with a high-density copper pillar array, the adhesive layer exhibits significant creep characteristics under the grinding temperature gradient. When the wafer thickness is reduced to below 50 microns, the adhesion between the adhesive layer and the copper pillar sidewall decays at a rate exceeding the critical threshold, resulting in periodic stress fluctuations in the center region of the wafer; the above fluctuations are transmitted radially to the edge fixed region of the wafer, forming an asymmetric shear stress distribution in the thickness direction of the wafer, and finally triggering a brittle fracture mode before the wafer backside grinding reaches the target thickness. The thinning adhesive tape and the surface structure of the bump ball grid array are well matched. The interpenetrating network structure improves the stress dispersion capability of the adhesive layer under dynamic load, reducing local stress concentration. The staged curing controls the crosslinking density gradient, achieving the synergy of strong adhesion on the surface and high elasticity inside. This structure significantly reduces the probability of micro-cracks and warping of the wafer during thinning, improving the mechanical integrity and processing stability of the ultra-thin wafer. At the same time, this scheme directly forms a thinning adhesive tape on the wafer, simplifying the process flow and improving production efficiency.
[0045] It can be understood that the acrylic acid forms hydrogen bonds with the hydroxyl groups in the first polymer network through the carboxyl groups, enhancing the cross-linking density within the adhesive layer and improving the overall cohesive strength of the adhesive layer. The reaction between the carboxyl groups and the isocyanate groups of the grafting monomers produces urethane structures, strengthening the interfacial bonding between the first polymer network and the second polymer network. The improved polarity matching allows the adhesive layer to form a uniform wetting spread on the wafer bump surface, reducing interfacial stress concentration. When the acrylic acid content is less than 1 part by weight, the polarity adjustment is insufficient; when the content exceeds 5 parts by weight, the excess carboxyl groups may increase the brittleness of the adhesive layer. By limiting the acrylic acid content to 1-5 parts by weight, the interfacial bonding force is ensured while maintaining the flexibility of the adhesive layer, thereby inhibiting the initiation of micro-cracks and wafer warping during the thinning process.
[0046] It can also be understood that by adding an appropriate amount of polar monomer acrylic acid to the debonding adhesive layer, the adhesion between the debonding adhesive tape and the surface of the bump ball mounting wafer can be enhanced, improving the stability during the thinning process. At the same time, due to the good reactivity of acrylic acid, it can form a more stable network structure with other components in the debonding adhesive layer, further improving the mechanical strength and heat resistance of the debonding adhesive layer; this improved debonding adhesive layer formula can better adapt to the surface characteristics of the bump ball mounting wafer, reducing the risk of problems such as delamination or air bubbles during the thinning process, thereby improving the yield and reliability of wafer thinning.
[0047] It should be noted that the substrate film can not only provide sufficient support to resist mechanical loads during the thinning process, but also disperse stress through moderate flexibility to avoid excessive stress concentration in the bump ball mounting area. For example, when a 100µm thick polyethylene terephthalate film is used, its rigidity can effectively maintain the flatness of the wafer, and further absorb dynamic stress during the grinding process through the viscoelastic deformation of the debonding adhesive layer.
[0048] It should be noted that the chemical stability of the polyethylene terephthalate film or polypropylene film can ensure that no thermal decomposition or reaction with the debonding adhesive layer occurs during the heat treatment process. When the release film thickness is controlled within the range of 15µm to 50µm, its flexibility can adapt to the curved structure of the fixed module 1 in the wafer thinning machine, ensuring that the substrate film and the wafer surface liquid film are tightly bonded after lamination. When pressure is applied in the lamination module 3, the elastic modulus of the release film can effectively buffer external stress, avoiding the generation of micro-cracks on the wafer surface due to excessive local pressure. Further, the thickness ratio of the release film to the substrate film is limited within a certain range, for example, when the substrate film thickness is 50µm to 150µm, the release film thickness is 10%-30% of the substrate film thickness, which can balance the support force and operational flexibility, reducing the probability of wafer warping during the thinning process.
[0049] It should be noted that during the heating treatment stage, the isocyanate of the trimer type reacts with the hydroxyethyl acrylate hydroxyl groups in the first polymer network to form stable urethane cross-linking bonds. During the ultraviolet light curing stage, 1-hydroxy cyclohexyl phenyl ketone absorbs light energy of a specific wavelength and then splits to initiate free radical polymerization of the soft monomer and the hard monomer. The two curing mechanisms act in stages, so that the adhesive layer on the wafer surface forms a gradient cross-linking structure, the area close to the base film is mainly rigid cross-linking formed by thermal curing, and the area close to the wafer surface is mainly flexible cross-linking formed by light curing. This structural difference enables the adhesive tape to resist interlayer peeling caused by grinding stress and at the same time buffer local stress concentration through the flexible area, thereby reducing the probability of micro-crack initiation.
[0050] It should be noted that isooctyl acrylate and n-butyl acrylate as soft monomers can reduce the glass transition temperature of the polymer due to their long-chain alkyl structure, and impart high elastic deformation capability to the adhesive layer; methyl methacrylate as a hard monomer can improve the compressive strength of the adhesive layer through a higher transition temperature and rigid side groups; and hydroxyethyl acrylate as a functional monomer can form hydrogen bonding with the surface of the base film through its hydroxyl functional group, thereby enhancing the interfacial bonding force. The synergistic use of isooctyl acrylate and n-butyl acrylate can balance the flexibility and cohesive strength of the adhesive layer at different temperatures, avoiding mechanical property fluctuations caused by a single soft monomer. The rigid segments of methyl methacrylate and the soft monomer segments form an interpenetrating network, inhibiting deformation failure of the adhesive layer due to local stress concentration during the thinning process. The hydroxyl groups of hydroxyethyl acrylate further promote chemical bonding with the base film, reducing the risk of interfacial peeling.
[0051] It should also be noted that during the preparation of the thinning adhesive tape, isooctyl acrylate and n-butyl acrylate are mixed in a specific ratio to form flexible segments through free radical polymerization, ensuring that the adhesive layer undergoes reversible deformation under grinding pressure to absorb mechanical energy; methyl methacrylate introduces rigid structures through copolymerization, limiting excessive deformation of the adhesive layer and maintaining the stability of support for wafer protruding structures; and the hydroxyl groups of hydroxyethyl acrylate react with the polar groups on the surface of the base film during the curing stage to form a dense interface layer, preventing delamination of the adhesive layer and the base film due to differences in thermal expansion coefficients. Through the combination of the above monomers, the adhesive layer can not only adapt to the changes in the micro-topography of the wafer surface during the thinning process, but also resist the combined action of shear force and compressive force, thereby reducing the probability of micro-crack and warpage.
[0052] It can be understood that, in the preparation of the first polymer network, the hydroxyethyl acrylate provides a hydroxyl reaction site as a functional monomer, and the isocyanatoethyl methacrylate is grafted with the hydroxyl group through the isocyanate group to form a crosslinked network. The molar amount of the grafting monomer is controlled to be 40-80 mol% of the molar amount of the functional monomer, so that the crosslinking points are uniformly distributed, which not only ensures the support strength of the adhesive layer on the wafer during the thinning process, but also avoids stress concentration caused by excessive crosslinking. For example, when the amount of the grafting monomer added is 60 mol%, the adhesive layer forms a three-dimensional network structure with toughness and rigidity after being heated and cured in the wafer thinning machine, effectively disperses the mechanical stress in the grinding process, and reduces the probability of micro-crack initiation.
[0053] It can also be understood that, by constructing a heat / light dual-cured interpenetrating polymer network with a double adhesion reduction mechanism, and combining the special preparation method of the thinning adhesive tape in the thinning machine, the present application reduces the probability of micro-crack initiation or warping in a specific area of the convex ball mounting wafer when the wafer is thinned using the adhesive tape. The thinning adhesive tape in the present application adopts a three-layer structure, similar to the conventional adhesive tape, but the core innovation lies in the adhesion reduction adhesive layer itself. Similarly, the thinning adhesive tape also includes a substrate film, which provides mechanical support, and in the present application, the substrate film is a polyolefin or polyethylene terephthalate film.
[0054] Example 1: In the specific embodiment of the present embodiment, the thinning adhesive tape includes a substrate film, an adhesion reduction adhesive layer, and a release film. The adhesion reduction adhesive layer includes, by weight fraction: 70 parts of a first polymer network, 25 parts of a second polymer network, 1 part of a thermal curing agent, and 4 parts of a photoinitiator; and further includes 3 parts by weight of a polar monomer. The first polymer network includes, by weight fraction: 77.5 parts of a soft monomer, 10 parts of a hard monomer, 10 parts of a functional monomer, and a grafting monomer. The second polymer network includes 1,5-pentanediol and fumaric chloride.
[0055] The preparation method of the first polymer network in the present embodiment is as follows: In a reaction kettle equipped with a stirrer, condenser, thermometer and nitrogen inlet, ethyl acetate was added as a solvent, the total weight of monomers was set to M grams, and the following monomers were added based on the total weight of monomers: soft monomers (77.5 parts by weight, of which isooctyl acrylate: n-butyl acrylate = 3:1 by weight), hard monomers (10 parts by weight of methyl methacrylate (MMA)), functional monomers (10 parts by weight of hydroxyethyl acrylate), and polar monomers (3 parts by weight of acrylic acid). The thermal initiator was a compound of benzoyl peroxide (BPO) and azobisisobutyronitrile (AIBN) in a weight ratio of 3:1, with a total amount of 0.8 parts by weight of the total weight of monomers. A semi-continuous solution polymerization method was used: 20 parts by weight of the monomer mixture and one quarter of the thermal initiator were added as a base material to the reaction kettle, nitrogen was introduced, and the temperature was raised to 75°C. The remaining monomer mixture and half of the thermal initiator were mixed uniformly, and then added dropwise over 2 hours using a peristaltic pump. After the addition was completed, the reaction was maintained for 3 hours. Finally, the remaining one quarter of the thermal initiator was dissolved in ethyl acetate and added to the reaction kettle, and the reaction was continued for 2 hours to ensure that the monomer conversion rate was greater than 99%. An acrylic ester copolymer (PSA-H) solution containing hydroxyl groups was obtained, with a weight average molecular weight (Mw) of about 700,000 g / mol and a glass transition temperature (Tg) of about -40°C.
[0056] It can be understood that the reaction occurring in the above process is a free radical polymerization reaction, and BPO and AIBN are decomposed by heat to generate free radicals, which initiate the opening of the carbon-carbon double bonds of each acrylic ester monomer and addition polymerization, forming a long chain of random copolymer.
[0057] Subsequently, the PSA-H solution was cooled to 50°C, and a catalyst, dibutyltin dilaurate (DBTDL), was added in an amount of 0.05 parts by weight of the weight of the subsequently added MMA. The molar amount of hydroxyethyl acrylate (HEA) copolymerized in the PSA-H was calculated, and an amount of MMA (grafting monomer) corresponding to 60 mol% of the molar amount of HEA was weighed, diluted with anhydrous ethyl acetate, and slowly added to the reaction kettle under nitrogen protection. After the addition was completed, the reaction was continued at 50°C. The characteristic absorption peak of isocyanate groups (-NCO) in the reaction solution was monitored by Fourier transform infrared spectroscopy (FTIR), and when the peak completely disappeared, the reaction was stopped, obtaining a first polymer network precursor (P-1) solution containing a side chain with a photocurable double bond and residual hydroxyl groups.
[0058] It can also be understood that in the above reaction, the urethane formation reaction occurs, in which the isocyanate groups (-NCO) in the MMA molecule undergo nucleophilic addition reaction with the hydroxyl groups (-OH) of the hydroxyethyl acrylate units on the side chain of the PSA-H, forming urethane bonds (-NH-COO-), thereby grafting the methyl methacrylate double bond-containing group to the polymer side chain, and DBTDL plays a catalytic role.
[0059] Afterwards, anhydrous tetrahydrofuran (THF) was added into a clean and dry reaction flask with stirring and dropping funnel. Under 3°C ice-bath and nitrogen protection, 1,5-pentanediol and triethylamine (2 times of fumaroyl chloride in molar amount) were added as acid binding agent. Fumaroyl chloride solution dissolved in anhydrous THF was added dropwise slowly (molar ratio of 1,5-pentanediol to fumaroyl chloride was 1.2:1). The dropping speed was controlled so that the reaction temperature did not exceed 5°C. After the dropping was completed, the temperature was slowly increased to 30°C and the reaction was continued at this temperature for 2.5 hours. After the reaction was completed, white hydrochloride of triethylamine precipitate was generated in the system, which was removed by filtration. The filtrate was distilled under reduced pressure to remove THF solvent, and the second polymer network precursor (P-2) in the form of colorless or light yellow viscous liquid was obtained.
[0060] It should be noted that in the above reaction, the acyl chloride group (-COCl) of fumaroyl chloride and the hydroxyl group (-OH) of 1,5-pentanediol undergo nucleophilic acyl substitution reaction to form ester bond (-COO-) and release HCl, at the same time, the carbon-carbon double bond in the fumaroyl chloride molecule is retained in the polyester backbone, the generated HCl is neutralized by triethylamine (base) to form triethylamine hydrochloride precipitate which is insoluble in THF, thereby promoting the esterification reaction to proceed in the forward direction.
[0061] Finally, the P-1 solution and P-2 prepared above were mixed under yellow light or light shielding condition, and according to the solid calculation, it was ensured that P-1 accounted for 70% of the total solid weight and P-2 accounted for 25% of the total solid weight after mixing. Then, 1 part of the trimer type isocyanate (for example, Desmodur N3300, as a thermal curing agent) and 4 parts of 1-hydroxycyclohexyl phenyl ketone (for example, Irgacure 184, as a photoinitiator) were added, accounting for 1 part of the total solid weight, and ethyl acetate was added as a solvent to adjust the final solid content and viscosity of the composition to be suitable for the subsequent coating process (for example, the viscosity was controlled at 5000-10000 mPa·s). A high-speed disperser was used to stir for at least 30 minutes to ensure that all components were dissolved and uniformly mixed without gel particles, and a final liquid adhesive composition was obtained.
[0062] In this embodiment, the adhesion-reducing adhesive layer further comprises 3 parts by weight of a polar monomer, which is acrylic acid.
[0063] In this embodiment, the substrate film is a polyolefin film, and the thickness of the substrate film is 100 µm.
[0064] In this embodiment, the release film comprises a polyethylene terephthalate film or a polypropylene film, and the thickness of the release film is 35 µm.
[0065] In this embodiment, the thermosetting agent includes a trimeric isocyanate, and the photoinitiator is 1-hydroxycyclohexylphenyl ketone.
[0066] In this embodiment, the soft monomer includes isooctyl acrylate and n-butyl acrylate, the hard monomer is methyl methacrylate, and the functional monomer includes hydroxyethyl acrylate.
[0067] In this embodiment, the grafting monomer includes isocyanate methacrylate, and the amount of grafting monomer added is 60 mol of the molar amount of the functional monomer.
[0068] As attached Figure 1 As shown, this embodiment provides a preparation method, which includes the following steps: Preparation of the first polymer network; Preparation of a second polymer network; A first polymer network, a second polymer network, a thermosetting agent, and a photoinitiator are mixed to obtain an adhesive composition; Inside the wafer thinning machine, an adhesive composition is coated onto the surface of the raised ball on the wafer to form a liquid film; The substrate film is laminated onto the liquid film; The release film is applied to the upper surface of the fixing module 1 inside the wafer thinning machine; Inside the wafer thinning machine, a wafer with a substrate film is mounted on a release film, and the laminated wafer is then heated to form a cured thinning tape directly on the wafer.
[0069] In this embodiment, the preparation of the second polymer network includes the following steps: 1,5-Pentanediol and triethylamine were dissolved in anhydrous tetrahydrofuran at 0-5°C under nitrogen protection. Add dropwise a fumarate chloride solution dissolved in tetrahydrofuran; Increase the temperature to 30°C and continue the reaction for 2.5 hours; After the reaction was completed, triethylamine hydrochloride was removed by filtration, and tetrahydrofuran was removed by vacuum distillation to obtain the second polymer network.
[0070] Based on the aforementioned method, the preferred implementation of this embodiment is as follows: A 12-inch silicon wafer with raised balls on the front is placed in a wafer thinning machine (see attached image). Figure 2) and precisely positioned. The liquid adhesive composition prepared in the preceding steps is uniformly coated on the convex bump surface of the wafer by the dynamic coating module 2, for example, using a precision slot coating or inkjet printing technology, to ensure complete coverage of all bumps and filling of the gaps therebetween, forming a liquid film of a predetermined thickness. The lamination module 3 is activated to release the pre-prepared 100 pm thick polyolefin (PO) substrate film from the reel, pass through the guide and pressure roller system, and precisely laminate onto the liquid film on the wafer surface, excluding air bubbles. At the same time or subsequently, the lamination module 3 laminates a 35 pm thick PET release film onto the upper surface of the fixing module 1 (in this embodiment, the surface will serve as a platform for subsequent heating and support). The positioning module 4 is activated to accurately pick up, flip over (and install (place) on the upper surface of the fixing module 1 with the substrate film and the liquid film (at this time, the substrate film faces upwards) laminated with the release film. At this time, the wafer is in contact with the release film below through the substrate film, and the heating function of the fixing module 1 is activated to heat the entire stack structure (fixing module 1 - release film - wafer - adhesive layer - substrate film) for heat treatment, for example, at 110°C for 3 minutes.
[0071] The main processes of the above steps are as follows: Solvent evaporation: the solvents such as ethyl acetate in the adhesive composition are volatilized by heat, and the liquid film is converted into a solid / semi-solid tack-reducing adhesive layer.
[0072] Thermally induced pre-crosslinking: heating triggers the reaction of the thermally cured agent (trimeric isocyanate) with the residual hydroxyl groups (-OH) on the side chain of P-1, forming urethane crosslinking bonds, which form a first heavy chemical crosslinking network inside the tack-reducing adhesive layer, giving the adhesive layer initial cohesive strength, shape stability, and firmly adhering to the substrate film and the wafer surface, and forming an interpenetrating network (IPN) structure.
[0073] It can be understood that controlling the reaction temperature at 0-5°C can inhibit the violent heat release of fumaric chloride and 1,5-pentanediol, avoiding local overheating leading to side reactions; nitrogen protection can prevent moisture in the air from hydrolyzing the reactants; anhydrous tetrahydrofuran as a solvent can improve the solubility of the reactants and maintain the inertness of the system; triethylamine is used to neutralize the generated hydrogen chloride, promoting the forward progress of the polycondensation reaction. The dropping speed of the fumaric chloride solution can be controlled by a constant pressure dropping funnel to ensure smooth reaction. After heating to 30°C for 2.5 hours, the polycondensation reaction can be fully completed, forming a second polymer network with crosslinking structure. The filtration step can remove the generated triethylamine hydrochloride precipitate, and the reduced pressure distillation can efficiently recover the solvent and avoid polymer degradation at high temperature.
[0074] Specifically, the initial reaction under low temperature environment can reduce the self-polymerization tendency of fumaric chloride, ensure the stability of the molar ratio of fumaric chloride and 1,5-pentanediol, and thus control the length of polymer chain and the crosslinking density. Nitrogen protection further isolates oxygen and moisture to avoid byproduct generation. Through staged temperature control, low-temperature mixing followed by high-temperature reaction, both the stability in the initial stage of reaction and the complete progress of the later polycondensation reaction are ensured. After the reaction is completed, the combination of physical filtration and reduced pressure distillation can efficiently remove byproducts and residual solvents, and finally a high-purity second polymer network is obtained. The network structure formed thereby is uniform, and after being mixed with the first polymer network, the thermal stability and mechanical strength of the tack-reducing adhesive layer can be improved, thereby providing more uniform support during wafer thinning and reducing the risk of micro-cracks and warping.
[0075] Overall, the liquid film uniformly covers the convex structure on the wafer surface through the coating module 2, and the lamination process of the base film and the liquid film is completed in the thinning machine, avoiding the lamination defects caused by physical handling of the pre-made adhesive tape and the wafer surface. During the heating process, the thermal curing agent and the photoinitiator trigger the crosslinking reaction of the first polymer network and the second polymer network, respectively, to form a double-network interpenetrating structure.
[0076] In the subsequent process, the wafer with the in-situ formed adhesive tape structure is sent to the thinning module for backside grinding to the target thickness, and after the thinning is completed, the tack-reducing adhesive layer is irradiated with high-energy ultraviolet light (e.g., main wavelength 365 nm) from the side of the base film; during the above process, the photoinitiator absorbs UV energy to generate free radicals, and at the same time, the free radical polymerization crosslinking of the methacrylic double bond on the PSA-UA side chain and the fumarate double bond on the UPEO main chain is initiated; this forms a second heavy chemical crosslinking network, which interpenetrates with the first heavy thermal curing network to form the final IPN structure. At the same time, the crosslinking shrinkage of the UPEO network causes the surface of the adhesive layer to have a micro concave-convex topography, greatly reducing the contact area with the wafer.
[0077] Example 2: The rest is the same as example 1, except that the weight parts of the first polymer network is 60, and the weight parts of the second polymer network is 15; The tack-reducing adhesive layer comprises 0.5 parts by weight of a thermal curing agent, 3 parts by weight of a photoinitiator, and 1 part by weight of a polar monomer.
[0078] Example 3: The rest is the same as example 1, except that the weight parts of the first polymer network is 80, and the weight parts of the second polymer network is 35; The tack-reducing adhesive layer comprises 1.5 parts by weight of a thermal curing agent, 5 parts by weight of a photoinitiator, and 5 parts by weight of a polar monomer.
[0079] Comparative Example 1: The rest is the same as example 1, except that the weight parts of the first polymer network is 55, and the weight parts of the second polymer network is 40; The tack-reducing adhesive layer comprises 1 weight part of thermal curing agent, 4 weight parts of photoinitiator, and 3 weight parts of polar monomer.
[0080] Comparative Example 2: The rest is the same as example 1, except that the weight parts of the first polymer network is 85, and the weight parts of the second polymer network is 10; The tack-reducing adhesive layer comprises 1 weight part of thermal curing agent, 4 weight parts of photoinitiator, and 3 weight parts of polar monomer.
[0081] Comparative Example 3: The rest is the same as example 1, except that the weight parts of the first polymer network is 70, and the weight parts of the second polymer network is 25; The tack-reducing adhesive layer comprises 0.3 weight part of thermal curing agent, 4 weight parts of photoinitiator, and 3 weight parts of polar monomer.
[0082] Comparative Example 4: The rest is the same as example 1, except that the weight parts of the first polymer network is 70, and the weight parts of the second polymer network is 25; The tack-reducing adhesive layer comprises 2 weight parts of thermal curing agent, 4 weight parts of photoinitiator, and 3 weight parts of polar monomer.
[0083] Comparative Example 5: The rest is the same as example 1, except that the weight parts of the first polymer network is 70, and the weight parts of the second polymer network is 25; The tack-reducing adhesive layer comprises 1 weight part of thermal curing agent, 2.5 weight parts of photoinitiator, and 3 weight parts of polar monomer.
[0084] Comparative Example 6: The rest is the same as example 1, except that the weight parts of the first polymer network is 70, and the weight parts of the second polymer network is 25; The tack-reducing adhesive layer comprises 1 weight part of thermal curing agent, 5.5 weight parts of photoinitiator, and 3 weight parts of polar monomer.
[0085] Comparative Example 7: The rest is the same as example 1, except that the weight parts of the first polymer network is 70, and the weight parts of the second polymer network is 25; The tack-reducing adhesive layer comprises 1 weight part of thermal curing agent, 4 weight parts of photoinitiator, and 0.5 weight parts of polar monomer.
[0086] Comparative Example 8: The rest is the same as Example 1, except that the weight parts of the first polymer network is 70 and the weight parts of the second polymer network is 25; The viscosity-reducing adhesive layer comprises 1 weight part of thermal curing agent, 4 weight parts of photoinitiator and 6 weight parts of polar monomer.
[0087] The components of each example and comparative example are shown in Table 1 below; Table 1
[0088] The performance test results of each example and comparative example are shown in Table 2 below; Table 2
[0089] In combination with the above table, Examples 1-3 show that when the P-1 content is in the range of 60-80 weight parts and the P-2 content is in the range of 15-35 weight parts, the adhesive layer can exhibit good comprehensive performance, especially the combination of Example 1, which achieves the best balance between hardness (75A), adhesion (8.5N) and low warpage value (<50µm); Comparative Example 1: P-2 content is too high, resulting in poor flowability of the adhesive composition, poor filling performance; the cured adhesive layer is too hard (92A), too brittle, and the internal stress is extremely large, resulting in serious warpage (>200µm) and micro-cracks of the wafer during thinning; Comparative Example 2: P-2 content is too low, the adhesive layer support is seriously insufficient, the hardness is only 58A, and under the grinding pressure, the wafer cannot be effectively supported, resulting in wafer deformation, warpage (>180µm) and cracking, and the adhesion is too low (5.1N), which cannot firmly fix the wafer.
[0090] In addition, Comparative Example 3: the thermal curing agent is seriously insufficient, resulting in insufficient crosslinking of the polymer network, the adhesive layer is too soft (53A), the adhesion is low (4.2N), and it cannot provide support, and more seriously, due to incomplete curing, residue is generated on the wafer surface after peeling.
[0091] Comparative Example 4: the thermal curing agent is excessive, resulting in too high crosslinking density, increased hardness (88A) and brittleness of the adhesive layer, and increased internal stress, which also leads to warpage (>160µm) during thinning.
[0092] Comparative Example 5: the photoinitiator is insufficient, resulting in insufficient initial curing (such as UV pre-curing), slow adhesion establishment (6.0N), affecting processing stability, and increased warpage value (<100µm) and micro-crack risk.
[0093] Comparative Example 6: Excessive photoinitiator leads to an excessively fast curing reaction, especially on the coated surface, which easily causes uneven shrinkage of the adhesive layer, generates internal stress, and worsens the warpage value (>130µm).
[0094] Comparative Example 7: The content of polar monomers was too low, resulting in insufficient wettability of the adhesive composition on the wafer surface and only slightly poor coating and filling properties. At the same time, the contribution to the adhesive force was limited (4.8N), resulting in poor fixation and warping.
[0095] Comparative Example 8: Excessive polar monomers resulted in excessively strong initial adhesion (10.8 N), which increased the difficulty of subsequent low-temperature peeling and may introduce additional stress due to excessive interfacial forces, leading to poor warpage (>140 µm).
[0096] In summary, the defined content ranges of each component are one of the key technical features for achieving the invention's objective of "reducing the probability of microcracks or warping in specific areas when using this tape for thinning operations on bump-balled wafers." As shown in Examples 1-3, excellent overall performance can be obtained when all components are within the scope of the claims. However, Comparative Examples 1-8 show that if the content of any component exceeds the defined range (whether below the lower limit or above the upper limit), a certain key performance of the tape (such as support hardness, adhesion, residue, and stress control) will significantly decrease, failing to meet the stringent requirements of ultra-thin wafer thinning processes.
[0097] Example 4: As attached Figure 2 As shown, this embodiment provides a wafer thinning machine, which includes: Fixed module 1 is used for fixed support; Coating module 2, which is used to coat the adhesive composition onto the surface of the raised ball on the wafer to form a liquid film; The lamination module 3 is used to laminate the substrate film onto the liquid film, and the lamination module 3 is also used to laminate the release film onto the upper surface of the fixing module 1 inside the wafer thinning machine. Positioning module 4, which is used to mount a wafer with a substrate film onto a release film; The fixing module 1 is also used to heat the laminated wafer to directly form a cured thinning tape on the wafer.
[0098] It can be understood that the coating module 2 adopts a precision nozzle array, the nozzle spacing matches the arrangement spacing of the wafer bump array, and the adhesive composition covers the bump gap. The covering module 3 comprises two independent pressure roller systems, one pressure roller applies constant pressure to adhere the substrate film to the surface of the liquid film, and the other pressure roller applies stepped increasing pressure to adhere the release film to the fixed module 1. The positioning module 4 is equipped with an optical alignment sensor, which adjusts the installation angle deviation by recognizing the positioning mark of the wafer edge. The fixed module 1 is built-in with a multi-zone independent temperature control unit, each temperature control unit corresponds to different areas on the wafer surface, and the heating temperature fluctuation range is controlled within ±1°C.
[0099] Specifically, the nozzle array of the coating module 2 moves along the radial direction of the wafer, and the glue amount is adjusted according to the preset program, so that the adhesive composition forms a liquid film with a thickness of 5-10µm in the bump gap. The first pressure roller of the covering module 3 adheres the substrate film to the liquid film with a pressure of 0.1-0.3MPa, and the initial pressure of the second pressure roller is 0.05MPa, which increases by 0.02MPa per revolution until it reaches 0.15MPa. The optical alignment sensor of the positioning module 4 detects the cross mark on the edge of the wafer, and when the angle deviation exceeds 0.5°, the fine adjustment mechanism is triggered to rotate the wafer to a deviation of less than 0.1°. The temperature control unit of the fixed module 1 divides the wafer into nine areas, the heating temperature of the central area is 80°C, and the peripheral areas are distributed with a gradient of 5°C per circle, and the heating time is 30 minutes. Through the synergistic effect of the above modules, the adhesive composition forms a uniform internal stress distribution during the curing process, reducing the probability of micro-cracks or warping caused by local stress concentration during wafer thinning.
[0100] As a preferred embodiment, the preferred implementation of the embodiment scheme is as follows: the fixed module 1 comprises a heating unit, which adopts a segmented temperature control mode to apply a gradient temperature field to the surface of the wafer after covering. Specifically, the preheating zone temperature is controlled at 40-50°C, the curing zone temperature is controlled at 80-100°C, and the cooling zone temperature is maintained at 25-30°C through a circulating water cooling system. The coating module 2 adopts a multi-point micro-nozzle array, the nozzle spacing is set to 0.5mm, the nozzle is kept perpendicular to the wafer surface, and the liquid film thickness is dynamically adjusted to 20-30μm through a pressure feedback system. The covering module 3 is equipped with a vacuum suction platform, the suction pressure is set to 0.05-0.1MPa, and the covering speed is controlled at 0.5-1.2m / min. The positioning module 4 integrates an optical alignment system, which uses a double-CCD visual sensor for three-dimensional coordinate calibration, and the positioning accuracy reaches ±2μm.
[0101] Through the technical scheme, the wafer thinning machine realizes in-situ forming of the thinning adhesive tape on the wafer surface by integrating the coating, lamination and positioning functions. The gradient temperature field control ensures uniform stress release of the adhesive layer during the curing process, and the segmented temperature control effectively avoids the deformation of the adhesive layer caused by local thermal expansion difference. The vertical nozzle array combined with dynamic pressure regulation ensures uniform filling of the liquid film in the bump gap, preventing bubble residue. The vacuum adsorption platform cooperates with optical positioning to accurately control the lamination quality of the substrate film and the wafer surface, eliminating the interface defects generated in the handling process of the traditional preformed adhesive tape. Therefore, the wafer obtains uniform support force distribution during the ultra-thin grinding process, significantly reduces the risk of micro-crack propagation caused by stress concentration, and suppresses the delamination tendency of the adhesive tape and wafer interface under high temperature conditions, improving the stability of the thinning process.
[0102] The above is only the preferred embodiment of the present application, and does not limit the patent scope of the present application, and any equivalent structure or equivalent process transformation using the content of the specification and drawings, or direct or indirect application in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A bump ball mount wafer thinning tape, characterized by, The thinning adhesive tape comprises a substrate film, an adhesive layer and a release film. The adhesive layer comprises, in parts by weight, 60-80 parts of a first polymer network, 15-35 parts of a second polymer network, 0.5-1.5 parts of a thermal curing agent and 3-5 parts of a photoinitiator. The first polymer network comprises, in parts by weight, 70-85 parts of a soft monomer, 5-15 parts of a hard monomer, 5-15 parts of a functional monomer and a grafting monomer. The second polymer network comprises 1,5-pentanediol and fumaric chloride.
2. The bump ball mount wafer thinning tape of claim 1, wherein, The adhesive layer further comprises 1-5 parts by weight of a polar monomer, and the polar monomer comprises acrylic acid.
3. The bump ball mount wafer thinning tape of claim 1, wherein, The substrate film is a polyolefin film or a polyethylene terephthalate film, and the thickness of the substrate film is 50 µm to 150 µm.
4. The bump ball mount wafer thinning tape of claim 1 or 3, wherein, The release film comprises a polyethylene terephthalate film or a polypropylene film, and the thickness of the release film is 15 µm to 50 µm.
5. The bump ball mount wafer thinning tape of claim 1, wherein, The thermal curing agent comprises a trimer type isocyanate, and the photoinitiator is 1-hydroxycyclohexyl phenyl ketone.
6. The bump ball mount wafer thinning tape of claim 1, wherein, The soft monomer comprises isooctyl acrylate and n-butyl acrylate, the hard monomer is methyl methacrylate, and the functional monomer comprises hydroxyethyl acrylate.
7. The bump ball mount wafer thinning tape of claim 1 or 6, wherein the adhesive layer is made of an acrylic-based pressure sensitive adhesive. The grafting monomer comprises isocyanatoethyl methacrylate, and the amount of the grafting monomer is 40-80 mol% of the molar amount of the functional monomer.
8. A method of manufacture, characterized by, The preparation method is used for preparing the raised ball wafer thinning adhesive tape according to any one of claims 1 to 7, and the preparation method comprises the following steps: preparing a first polymer network; preparing a second polymer network; mixing the first polymer network, the second polymer network, a thermal curing agent and a photoinitiator to obtain an adhesive composition; coating the adhesive composition on the surface of the raised ball of the wafer in a wafer thinning machine to form a liquid film; laminating the substrate film on the liquid film; laminating the release film on the upper surface of the fixed module in the wafer thinning machine; installing the wafer with the substrate film on the release film in the wafer thinning machine to perform a heating treatment on the laminated wafer to directly form a cured thinning adhesive tape on the wafer.
9. A method of manufacture according to claim 8, wherein, The preparation of the second polymer network comprises the following steps: dissolving 1,5-pentanediol and triethylamine in anhydrous tetrahydrofuran under nitrogen protection at 0-5 °C; dropping a fumaric chloride solution dissolved in tetrahydrofuran; continuing the reaction at 30 °C for 2.5 hours; after the reaction is completed, removing triethylamine hydrochloride by filtration, and then removing tetrahydrofuran by reduced pressure distillation to obtain the second polymer network.
10. A wafer thinning machine characterized by, The wafer thinning machine is used for implementing the preparation method according to claim 9 and / or preparing the raised ball wafer thinning adhesive tape according to any one of claims 1 to 7, and the wafer thinning machine comprises: a fixed module for fixing and supporting; a coating module for coating the adhesive composition on the surface of the raised ball of the wafer to form a liquid film; a laminating module for laminating the substrate film on the liquid film, and the laminating module is also used for laminating the release film on the upper surface of the fixed module in the wafer thinning machine; a positioning module for installing the wafer with the substrate film on the release film. The fixed module is further configured to perform heating treatment on the wafer after the lamination to form the solidified thinning adhesive tape directly on the wafer.
Citation Information
Patent Citations
Pressure-sensitive adhesive for wafer grinding and preparation method thereof
CN103571367A
UV viscosity-reducing adhesive for electronic device manufacturing process and preparation method of UV viscosity-reducing adhesive
CN116536023A
Acrylate adhesive, adhesive composition and protective film
CN118956299A
Cited By
Convex ball-mounting wafer thinning composite adhesive tape and preparation method thereof
CN122168192A
A convex ball-planting wafer thinning composite adhesive tape and a preparation method thereof
CN122168192B